Fish biomass in relation to water quality index as an indication of fisheries productivity of four selected fish species along the Galas River, Kelantan, Malaysia - Hashim, Rohasliney; Noor Fakira , Ismail (Elsevier, 2015)
This study aimed to assess the relationship between river water quality and fish biomass along the Galas River, Kelantan. Fish were collected using gill nets set along the Galas River from 2008 to 2009. Water Quality Index (WQI) data were obtained from the Department of Environment (DOE), Malaysia. A two-way ANOVA repeated-measures test, simple linear regression, and Spearman correlation were used to analyse the data. There was a significant difference in fish biomass in relation to water quality along the Galas River among stations and years. There was a weak correlation between WQI and fish biomass of four selected fish species in the Galas River from 2008 to 2009 (r = 0.22; p > 0.05)